Higher-speed Trapped-oil Pressure Research and Relief-groove Invention for Gear Pump - Changming Wen; Yulong Li (Jixie chuandong)
To achieve the abundant relief of high-speed trapped-oil for gear pump，based on the same tooth profile parameters and working conditions，the experiment，simulation and theoretical analysis are carried out successively. Secondly，the shape，position and size of the new groove are given. Finally，the case calculation of trapped-oil pressure were carried out. The results show that the theoretical analysis is correct by the consistency of experiment，simulation and theoretical results. Under the speeds of 1 000 r/min， 3 000 r/min， 5 000 r/min and 0.03 mm small backslash， the increase rate of the pressure peak of the new groove and the rectangular groove are 1.75%，15%，41.5% and 9.50%，85% and 236.25% respectively. It shows that the rectangular groove can meet the relief requirement of trapped-oil under low speeds， and the new groove can meet the relief requirement of trapped-oil under medium speeds. Under the high speeds of 5 000 r/min and 0.2 mm large backlash， the pressure increase rate of the new groove is 22.75%， which indicates that it can meet the relief requirement under high speed.